Collaborative Governance in Digital Transformation Policy Implementation for MSMEs in Jakarta: A Socio-Legal Perspective - Sigit Wijatmoko; Ika Sartika; Rosmery Elsye (Unissula, 2025)
This study investigates the role of collaborative governance in the digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Jakarta Province, focusing on the Jakarta Entrepreneur ecosystem, which comprises 372,540 enterprises. Based on Jakarta Governor Regulation Number 2 of 2020, the study aims to understand how cross-sector collaboration can help drive the digital transformation of MSMEs and thereby contribute to strengthening Jakarta’s competitiveness as a Sustainable Global City. Using a qualitative approach, this research explores collaboration mechanisms, factors inhibiting MSME digital transformation, and constructs a new collaborative model to empower MSMEs. Findings highlight the importance of facilitative leadership, institutional design, and supportive structures. Main obstacles include limited technology infrastructure, low digital literacy, and weak skills among MSMEs. The implementation of Governor Regulation Number 2 of 2020 has not yet been fully effective in addressing these barriers. The study suggests policy revision and enhanced collaboration through collaborative forums, communication, and transparency. It proposes the Integrated Partnership Model for Digital Transformation of MSMEs (KTDSU), which integrates public, private, academic, civil society, and media sectors. The model emphasizes technological innovation and social empowerment to help MSMEs grow and become more competitive in the digital era.